A study on consumers awareness and consumption patterns of green food among students in Universiti Utara Malaysia - Nur Hazirah, Mohamad Janai (2016)
Food is the basic need to all human being in world and they have the right to consume and choose the safe products. Health consciousness, food safety, and environment consciousness are the main reasons why the consumers progressively aware about the products they consume. Since the nature is getting worst due to environment problem, it has become public concern to introduce green concept in many countries. In Malaysia, the concept of green food still new to consumers, however the demand of the product is increase time by time. The objective and aim of the research is to identify the consumers’ awareness and green food consumption patterns among Undergraduate students in Universiti Utara Malaysia. Even the awareness of food quality and eating patterns could influence students mentally and physically. The research is focus on students because they are possessed important towards the environment and showing their responsibilities. Accordingly, this paper aims to discuss eating consumption practices among university students and their perception of proper feeding practices .The research used questionnaire and 400 respondents are needed to complete the data survey. In this way, it can help the policy makers to manage in formulating and implement the strategies to enhance the knowledge among the consumers especially the students. The implications of the theoretical and managerial as well as the recommendation are discussed in the study